Dutch Books, Indicative Conditionals, and Rational Updating - McNamara, Calum; Zhang, Xueyin (Snow) (Proceedings of the Amsterdam Colloquium, 2024)
Intuitive credence judgments in cases involving indicative conditionals sometimes seem to conflict with the claim that you should update your credences by conditionalization. For this very reason, however, these credence judgments appear Dutch-bookable. After all, a classic result of Lewis (1999) seems to show that, if you update your credences in any way that conflicts with conditionalization, then a cunning bookie can always lead you into a Dutch book situtation. In this paper, we argue that—despite appearances—the intuitive credence judgments in the relevant cases may not, in fact, be Dutch-bookable. The reason is that the Lewisian Dutch book argument for conditionalization turns out to rest on a hidden assumption. We drop that assumption, and give more general Dutch book results. Our results vindicate conditionalization only in special cases.